ANALISIS FINANCIAL DISTRESS PADA PERUSAHAAN PERTAMBANGAN BATU BARA YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2017-2018 - Reza Septian Pradana (Universitas Medan Area, 2020)
This study aims to identify financial distress for coal mining firms registered in Indonesia Stock Exchange and analyze the factors that influent. This study uses methodological logistic regression analysis. The result of analyzing annual financial report 23 coal mining firms registered in Indonesia Stock Exchange period 2017-2018 is that 5 firms get financial distress. The result of estimation using logistic regressionshows that firm size and Debt to Equity Ratio (DER) significantly influent to the opportunity of coal mining firms gets financial distress. Thus, coal mining firms registered in Indonesia Stock Exchange period 2017-2018 need to enhance asset and use equity more than debt for firm’s funding.